The assessment of map generated from unmanned aerial vehicle (UAV) images using built-in GPS in camera as a references coordinate / Noraswani Khairuddin - Khairuddin, Noraswani (2020)
Unmanned Aerial Vehicle (UAV) is an aircraft without needing a pilot on board. It can be controlled remotely or autonomously fly according to the program which fixed by human. The output produced is as precise as the conventional survey because it offers centimetre accuracy. Besides, there are variety of useful information about the ground surface which can be extracted without having to spend a lot of time. This information can be generated based on the selection of parameters chosen during flight planning and data processing. The aim for this project is to determine the accuracy assessment of map created from UAV images using built-in GPS in camera as a reference coordinates. Study area chosen for this project is in UiTM Perlis. The methodology applied for this project is the UAV Photogrammetry module where it includes processing of images by using Agisoft Photo Scan software after image acquisition from flying the drone. There are two method of processing which are direct geo-referencing and geo-referencing by using GNSS values. The analysis was carried out as the indication that Ground Control Point (GCP) is necessary in enhancing the accuracy of the output. These analysis was shown in both qualitative and quantitative in order to support the importance of utilizing GCP in this survey. According to the result obtained, the output produced without applying GCP is precise but not accurate as it does not in the right position.